Why We Need Art: Philip Bromberg's "Other Ways of Knowing". Issue 2 (3rd April 2022) - Ceccoli, Velleda C.
Abstract: This essay addresses some of Philip Bromberg's ideas regarding "other ways of knowing" as important, implicit communications that can yield information about early attachment(s), and relational ruptures. Because they convey meaning through the senses and not through spoken language, they potentially serve as a means of perceptual symbolization. Bromberg privileged implicit knowing in his clinical work, and considered art in all of its manifestations, as well as dreams in their embodied/imaginal qualities, to be central to procedural memory and implicit relational knowing.